Systematically varied interfaces of continuously reinforced glass fibre/polypropylene composites: Comparative evaluation of relevant interfacial aspects (eXPRESS Polymer Letters, 2010)
Interface related mechanical properties of unidirectional continuous glass fibre (GF)/polypropylene (PP) composites made of commingled yarns have been systematically studied according to a three level, three-factor factorial design. The three systematically varied factors comprised different silane coupling agent and film former contents in GF sizings as well as a varying GF diameter. Besides the statistical evaluation of those main effects on the transverse tensile and compression shear strengths of the composites, interfacial shear strength measurements on model composites have been performed. The latter ones as well as the results of the dynamic mechanical thermal analysis support the statistical significance of sizing components, the sizing content on the GF, and GF diameter for the mechanical properties of the composites. This highlights the interplay of proper sizing formulation and reproducible GF-spinning conditions, as both affect the interfacial bonding of continuously reinforced GF/PP composites.